2023
DOI: 10.3390/antiox12040959
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Melatonin Secretion, Oxidative Stress and Metabolic Syndrome in Night Shift Work

Abstract: Metabolic syndrome has been associated in many studies with working in shifts. Even if the mechanistic details are not fully understood, forced sleep deprivation and exposure to light, as happens during night shifts, or irregular schedules with late or very early onset of the working program, lead to a sleep–wake rhythm misalignment, metabolic dysregulation and oxidative stress. The cyclic melatonin secretion is regulated by the hypothalamic suprachiasmatic nuclei and light exposure. At a central level, melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Melatonin is a human hormone produced by the pineal gland, which has many functions such as regulating the circadian rhythm and increasing the immunity. Hohor et al 34 . found that the levels of melatonin and its metabolites in shift workers exposed to light at night showed a gradual decline.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Melatonin is a human hormone produced by the pineal gland, which has many functions such as regulating the circadian rhythm and increasing the immunity. Hohor et al 34 . found that the levels of melatonin and its metabolites in shift workers exposed to light at night showed a gradual decline.…”
Section: Discussionmentioning
confidence: 98%
“…Second, sleep is a key mechanism for maintaining optimal immune 37 , cellular 38 , metabolic 39 , and endocrine 40 , and each neurophysiological dysfunction is associated with carcinogenic pathways. In addition, the disorder of sleep and rest may affect the innate and acquired immune capacity, increase reactive oxygen species (ROS), lead to DNA damage and disrupt metabolic function, leading to the occurrence of tumors 34 . Not only that, some common carcinogenic factors, smoking, obesity, less exercise and other people are more likely to develop sleep disorders, which also explains the higher incidence of tumors 41 .…”
Section: Discussionmentioning
confidence: 99%